Heparin-Induced Thrombocytopenia under Mechanical Circulatory Support by Large Impella for Acute Cardiogenic Shock - Yukiharu Sugimura; Sebastian Bauer; Moritz Benjamin Immohr; Derik Franz Hermsen; Ralf Westenfeld; Udo Boeken; Hug Aubin; Igor Tudorache; Artur Lichtenberg; Payam Akhyari (Journal of Cardiovascular Development and Disease, 2021)
Despite the critical feature of heparin-induced thrombocytopenia (HIT) for patients on mechanical circulatory support, reports on its incidence and outcome are still scarce. Thus, we report on clinical features of HIT in patients under Impella 5.0 or 5.5 (Abiomed Inc., Danvers, MA, USA) (Impella 5+) support for acute cardiogenic shock (CS) by focusing on observed thrombotic events. Between November 2018 and December 2020, a total of 56 consecutive patients were enrolled in a single-center retrospective study. A total of 21 patients (37.5%) were tested for HIT, and 6 (10.7%) proved positive for HIT at 10.5 ± 2.89 days after the first heparin administration during current admission. Interestingly, thrombocyte counts dropped under Impella support in all groups (all cases, no HIT test, and HIT negative group: p < 0.001, HIT-positive group: p = 0.001). All HIT-positive patients were switched from heparin to argatroban. HIT-associated thrombotic events were observed in two cases resulting in Impella dysfunction due to pump thrombosis (n = 1) and left ventricular (LV) thrombus formation (n = 1). Under large Impella support, the prevalence of HIT was relatively high. Further, thrombocytopenia does not deliver a high specificity in the setting of Impella 5+ support. Considering HIT manifestation, a routine HIT test may be considered to avoid critical thrombotic adverse events.